2020
DOI: 10.1111/pre.12438
|View full text |Cite
|
Sign up to set email alerts
|

Status, morphology, and phylogenetic relationships of Iyengaria (Scytosiphonaceae, Phaeophyceae), a brown algal genus with a disjunct distribution in the Indian Ocean

Abstract: The taxonomy, classification, and phylogenetic relationships of the brown seaweed genus Iyengaria with other members of the family Scytosiphonaceae remain poorly understood. In this study, we addressed some problems in the systematics (taxonomic and classification status) and phylogenetic position of Iyengaria based on our studies on the generitype Iyengaria stellata from Kuwait and South Africa. We confirm that I. stellata is conspecific with Colpomenia capensis based on molecular and morpho-anatomical data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Problems of paraphyly or polyphyly in some scytosiphonacean genera including Colpomenia have been shown in previous molecular phylogenetic studies using not only a single gene but also multiple genes (Santiañez et al 2018(Santiañez et al , 2020. Similarly, members of the genus Colpomenia did not form a clade in our analyses that is the clade of C. peregrina, C. claytoniae, C. expansa, and C. borea was well supported but separated from other Colpomenia species including the generitype C. sinuosa.…”
Section: Phylogeny Of Cox3 and Rbclsupporting
confidence: 41%
See 1 more Smart Citation
“…Problems of paraphyly or polyphyly in some scytosiphonacean genera including Colpomenia have been shown in previous molecular phylogenetic studies using not only a single gene but also multiple genes (Santiañez et al 2018(Santiañez et al , 2020. Similarly, members of the genus Colpomenia did not form a clade in our analyses that is the clade of C. peregrina, C. claytoniae, C. expansa, and C. borea was well supported but separated from other Colpomenia species including the generitype C. sinuosa.…”
Section: Phylogeny Of Cox3 and Rbclsupporting
confidence: 41%
“…Problems of paraphyly or polyphyly in some scytosiphonacean genera including Colpomenia have been shown in previous molecular phylogenetic studies using not only a single gene but also multiple genes (Santiañez et al . 2018, 2020). Similarly, members of the genus Colpomenia did not form a clade in our analyses that is the clade of C .…”
Section: Discussionmentioning
confidence: 99%
“…Total genomic DNA was extracted from cultured thalli, following the methods described in Santiañez et al (2020). Polymerase chain reaction (PCR) amplification was performed for rbcL and psaA genes, using TaKaRa Ex Taq DNA polymerase (Takara Bio, Otsu, Japan) and primers which were previously published (Kogame et al 1999;Yoon et al 2002) or designed in this study as shown in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the family Scytosiphonaceae Farlow (Ectocarpales, Phaeophyceae) has received a fair amount of attention, and major taxonomic revisions have been made with the help of molecular data (Santiañez et al., 2020; Santiañez & Kogame, 2019, 2022; Santiañez, Lee, et al., 2018; Santiañez, Macaya, et al., 2018; Santiañez & West, 2019; Santiañez & Wynne, 2019). According to AlgaeBase (Guiry & Guiry, 2023), at the time of writing, the family Scytosiphonaceae consisted of 65 species belonging to 20 genera— Chnoospora J. Agardh (2 species), Colpomenia (Endlicher) Derbès & Solier (10 species), Dactylosiphon Santiañez, K.M.…”
Section: Introductionmentioning
confidence: 99%